Emerging Science and Technology Options in Monitoring Invasive Tunicate Colonization - Galloway, Claire (My University, 2017)
Marine invasive species are a growing problem exacerbated by the evolution and emergence of marine technology and modes of transportation. Current tracking and observation methods of tunicate colonization relies on the observations of trained human divers, which can be extremely costly, time-consuming, create inconsistent outcomes between individual divers, and require advanced permitting when preformed in busy ports and marine settings. Most other surveying equipment is expensive and requires a technological and mechanical skill set. Monitoring these species via embedded systems such as Remotely Operated Vehicles can help to better understand the qualities that make them so invasive, as well as potentially how to eradicate them without damaging native species or their ecosystems. This project focuses on a market competition of technology components used in monitoring the establishment and growth of invasive tunicate colonies in the Puget Sound, through the compared performance, suitability, and cost-effectiveness of each component. A three-part approach was created to evaluate all components affectively. From this process, it was concluded that a mid-cost Open ROV trident coupled with open source GIS and photo-editing software is a viable technique for monitoring the establishment and colonization of tunicates.
Keywords: tunicates; Puget Sound; invasive species